Physical health status in middle age on cognitive function: Literature review - Fauziyyah, Jihan Nafisah; Sabila, Misna Zakiyus; Septiani, Riswanti; Istianah, Istianah (PT WIM Solusi Prima, 2025)
This study aimed to systematically examine the relationship between physical health status in middle age and cognitive function. This systematic literature review was conducted following the PRISMA guidelines, with searches such as PubMed/MEDLINE, Scopus, Web of Science, PsycINFO, and CINAHL for articles published between 2020 and 2024. The inclusion criteria focused on original studies involving individuals aged 40-65 years, measuring physical health indicators, and evaluating cognitive function. 7 relevant articles were analyzed and narratively synthesized. The findings showed that various aspects of physical health status in middle adulthood were significantly associated with cognitive function. Body composition (BMI, muscle mass, visceral obesity) and metabolic health (fasting blood glucose levels) were consistently associated with cognitive performance and the risk of cognitive impairment. Cardiovascular health, represented by diastolic blood pressure, also affected brain structure and cognitive function. The relationship between physical activity and balance with cognition is variable, but some evidence suggests benefits of moderate-intensity physical activity and mind-body exercises such as Tai Chi. Other contextual factors such as education and early life conditions also play a role in cognitive resilience. In conclusion, interventions targeting weight management, metabolic health, cardiovascular health, and physical activity promotion in middle age have great potential to maintain optimal cognitive function. Further longitudinal studies are needed to confirm causal relationships and explore underlying mechanisms in more depth.